The Effect of Oral Metronidazole in the Prevention of Preterm Labour among Pregnant Women with Bacterial Vaginosis (Global Journal of Medical Research, 2014)
Aim of the study: To evaluatethe effectiveness of oral metronidazole in prevention of preterm labouramong pregnant women with bacterial vaginosis. Settings and study design: An experimental (longitudinal-prospective) study done in Tikrit city between April 2011 and April 2012. Methods: A total number of 50 pregnant women in their midtrimester were included in the study, they received oral metronidazole 200 mg orally in two divided doses for 7 days,selection criteria include pregnant women with singleton viable pregnancy in midtrimester with intact membranes. Demographic profile and prolongation of pregnancy and neonatal outcome were recorded is special forms. Results: Oral metronidazole was not effective in prolongation of pregnancy despite its efficacy in eradicating bacterial vaginosis. Conclusion: Our findings suggest that second trimester screening and treatment of bacterial vaginosis during pregnancy with oral metronidazole is not effective regarding prolongation of pregnancy and preventing adverse neonatal outcome.
Keywords: metronidazole; preterm labour; bacterial vaginosis